Surveillance Data Highlights Feed Form, Biosecurity, and Disease Control as Significant Factors Associated with Salmonella Infection on Farrow-to-Finish Pig Farms - Argüello, Hector; Manzanilla, Edgar G.; Lynch, Helen; Walia, Kavita; Leonard, Finola C.; Egan, John; Duffy, Geraldine; Gardiner, Gillian E.; Lawlor, Peadar G. (Frontiers in Microbiology, 2018)
Among the zoonotic pathogens affecting pigs, Salmonella stands out due to the high number of human cases linked to pork consumption. In the last two decades many countries have put considerable effort into the control of the infection by surveillance and control strategies on farm. Despite this effort, many herds still have a high Salmonella prevalence and they require guidance to address this problem. The present study, using the serological surveillance data of finishing pigs from the Irish National pig Salmonella Control Programme, aimed to highlight factors associated with increased risk or that might mitigate Salmonella occurrence on farm. A questionnaire with 33 questions regarding herd characteristics, management, feeding, biosecurity and health was completed for 61 individual herds. After the multivariate analysis by linear regression, nine variables were retained in the final model and linked to herd seroprevalence. Home produced-feed linked to the use of meal showed an eight points reduction in Salmonella prevalence compared to purchased feed (p=0.042). Different biosecurity measures were associated to lower seroprevalence. Changing of footwear from outside to inside the farm decreased seroprevalence nearly 20 units (p=0.014) and policies not permitting access to the farmyard to feed trucks (p=0.048) or avoiding the presence of cats on the farm (p=0.05) were estimated in 10 units less of seroprevalence. In contrast, the lack of perimeter fence increased the chance to have higher seroprevalence in five units (p=0.05). Finally, intestinal diseases such as swine dysentery (p=0.044) and E. coli diarrhoea (p=0.1) were estimated to increase Salmonella prevalence in approximately 20 and 10 units respectively, demonstrating the importance of controlling other enteric pathogens in an on-farm Salmonella control programme. These results show the usefulness of surveillance data to improve on-farm control and confirm that Salmonella infection in pigs is multi-factorial and the approach to its control should be multifaceted.